2014
DOI: 10.1016/j.ijrobp.2014.03.034
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 1/2 and Biomarker Study of Preoperative Short Course Chemoradiation With Proton Beam Therapy and Capecitabine Followed By Early Surgery for Resectable Pancreatic Ductal Adenocarcinoma

Abstract: Purpose To evaluate the safety, efficacy and biomarkers of short-course proton beam radiation and capecitabine, followed by pancreaticoduodenectomy in a phase 1/2 study in pancreatic ductal adenocarcinoma (PDAC) patients. Methods and Materials Patients with radiographically resectable, biopsy-proven PDAC were treated with neoadjuvant short-course (2-week) proton-based radiation with capecitabine, followed by surgery and adjuvant gemcitabine. The primary objective was to demonstrate a rate of toxicity grade ≥… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 100 publications
(54 citation statements)
references
References 40 publications
3
49
0
2
Order By: Relevance
“…The expression of CXCR7 was found to be associated with tumor grade and inversely correlated with tumor size in patients with pancreatic adenocarcinoma (56). In addition, stromal expression of CXCR7 was associated with significantly worse survival outcomes in pancreatic cancer patients that were treated with neoadjuvant chemoradiotherapy followed by surgery and adjuvant gemcitabine treatment (53). These observations suggest that CXCR7 has a potential role in the tumorigenesis of pancreatic adenocarcinoma, and that CXCR7 is involved in cell migration and invasion in pancreatic cancer.…”
Section: Liver Cancermentioning
confidence: 83%
See 2 more Smart Citations
“…The expression of CXCR7 was found to be associated with tumor grade and inversely correlated with tumor size in patients with pancreatic adenocarcinoma (56). In addition, stromal expression of CXCR7 was associated with significantly worse survival outcomes in pancreatic cancer patients that were treated with neoadjuvant chemoradiotherapy followed by surgery and adjuvant gemcitabine treatment (53). These observations suggest that CXCR7 has a potential role in the tumorigenesis of pancreatic adenocarcinoma, and that CXCR7 is involved in cell migration and invasion in pancreatic cancer.…”
Section: Liver Cancermentioning
confidence: 83%
“…CXCR7 expression has been identified in pancreatic adenocarcinoma in vitro and in vivo, along with upregulation of the CXCR7 gene on oligonucleotide microarrays (53)(54)(55)(56)(57)(58)(59). The expression of CXCR7 was found to be associated with tumor grade and inversely correlated with tumor size in patients with pancreatic adenocarcinoma (56).…”
Section: Liver Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Local progressionfree survival, progression-free survival, and overall survival rates were 81.7, 64.3, and 76.8 %, respectively [88]. To shorten treatment times, hypofractionated proton radiotherapy is being evaluated within clinical trials: A dosing scheme of 5×5 Gy E has shown only 4.1 % of Grade 3 side effects with favorable local control; KRAS-status and high CXCR7-expression, circulating CEA, CA 19-9 as well as HGF-levels correlated with poor outcome [89]. Randomized trials comparing with advanced photons (IMRT, SBRT, or other) are still lacking.…”
Section: Novel Rt Conceptsmentioning
confidence: 99%
“…The major advantage of proton beam over conventional radiation is that the energy distribution of protons can be directed and deposited in tissue volumes designated by the physicians in a 3D pattern. Investigators from Massachusetts General Hospital first reported the results of a Phase I/II study of preoperative short-course proton beam radiation with capecitabine as neoadjuvant treatment for pancreatic cancer [84,85]. These results were especially promising when compared with a similar study using the same dose escalation schema and photon radiation in which unexpected intraoperative complications occurred (63 vs 27%, respectively) [86].…”
mentioning
confidence: 99%